2010
DOI: 10.1007/s12098-010-0096-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of pyridoxine and pyridostigmine in children with vincristine-induced neuropathy

Abstract: Four children with vincristine (VCR)-induced neuropathy are being reported. All cases were followed with the diagnosis of acute lymphoblastic leukemia. Two were boys aged between 2 and 13 year. Electromyographic examination consisted of sensoriomotor polyneuropathy with axonal involvement in three patients. In another patient, it consisted of motor axonal polyneuropathy. In all patients, pyridoxine and pyridostigmine were successfully used in the treatment of VCR-induced neuropathy. They recovered completely w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…Pyridoxine and pyridostigmine has been associated with an early recovery (within 1–2 weeks) of vincristine induced peripheral neuropathy in a case series of patients [12]. The role of glutamic acid in decreasing vincristine induced neurotoxicity has been analyzed in some studies involving rat model [13], however this was not found to be effective when used in a patient with vincristine induced vocal cord palsy [14].…”
Section: Discussionmentioning
confidence: 99%
“…Pyridoxine and pyridostigmine has been associated with an early recovery (within 1–2 weeks) of vincristine induced peripheral neuropathy in a case series of patients [12]. The role of glutamic acid in decreasing vincristine induced neurotoxicity has been analyzed in some studies involving rat model [13], however this was not found to be effective when used in a patient with vincristine induced vocal cord palsy [14].…”
Section: Discussionmentioning
confidence: 99%
“…S. Akbayram et al в клиническом описании лечения 4 пациентов с ВНК-индуцированной нейро-патией отметили положительный эффект применения пиридоксина (в дозе 150 мг/м 2 /сут) и пиридостигмина (в дозе 3 мг/кг/сут) на фоне прекращения введения ВНК. Улучшение неврологической симптоматики от-мечалось у всех пациентов в периоде от 1-й до 2-й не-дели лечения [14]. В описаниях клинических наблюде-ний ВНК-индуцированного птоза также проводилось лечение КН с применением пиридоксина и пиридо-стигмина.…”
Section: пораженныеunclassified
“…Mouse models implicating 5-HT2A receptor involvement in neuropathic pain have led to interest in the use of SNRIs though clinical evidence in humans is lacking (Marchand et al 2003 ;Thibault et al 2008 ). Case reports have discussed use of pyridoxine and pyridostigmine with some effect but larger case series or trials have not been performed (Akbayram et al 2010 ). Other chemotherapeutic agents linked to neuropathic pain syndromes include other vinca alkaloids (vinblastine, vinorelbine), platinum agents (cisplatin, oxaliplatin), taxanes (paclitaxel, docetaxel) and newer agents like bortezomib (Han and Smith 2013 ).…”
Section: Vincristine-related Peripheral Neuropathymentioning
confidence: 99%